Pseudomonas septicaemia: in a case of pancytopenia - Nagori, Yusuf; Chandakb, Darshan; Dube, Sunil; B., Vatsal (International Journal of Research in Medical Sciences, 2017)
Pseudomonal infection is a rare condition with multiple systemic complications. A new condition of interest is ecthyma gangrenosum in a patient with pseudomonas septicaemia with pancytopenia and megaloblastic anaemia. So here we present you the case of Ecthyma gangrenosum in a 20-year-old female with pseudomonas septicaemia due to pancytopenia. A high degree of clinical suspicion is required, but a tissue sample is ultimately necessary for definitive diagnosis.